Remaining Agile in the COVID-19 pandemic healthcare landscape – How we adopted a hybrid telemedicine Geriatric Oncology care model in an academic tertiary cancer center. Issue 6 (July 2022) - Chen, Matthew; Mohd Said, Noorhanah; Mohd Rais, Nydia Camelia; Ho, Francis; Ling, Natalie; Chun, Meiling; Ng, Yean Shin; Eng, Wan Nghee; Yao, Yao; Korc-Grodzicki, Beatriz; Pang, Angela
Abstract: Introduction: The COVID-19 pandemic has impacted healthcare on an unprecedented scale, with healthcare resources being channeled into managing the devastating effects of the outbreak. Healthcare provision for vulnerable older adults has also been affected by lockdowns and suspension of selected medical services worldwide. In our tertiary cancer center, the National University Cancer Institute, Singapore (NCIS), our Geriatric Oncology (GO) service for older adults with cancer was halted for five months. In this paper, we describe the adoption of a hybrid telemedicine model by our GO service to continue care provision for older adults in the midst of the pandemic. Materials and Methods: Comprehensive geriatric assessments (CGA) were done via telemedicine and virtual multidisciplinary discussions were held prior to the patients' clinic visits. A hybrid telemedicine consultation allowed geriatricians and oncologists, segregated in different sites during the pandemic, to provide a hybrid physical and video geriatric oncology consultation. Scheduled phone follow ups by GO nurses helped to monitor patients for treatment-related toxicities and geriatric syndromes. Results: Two hundred fifty patients were enrolled in the program from July 2020 to August 2021. All were assessed with a CGA, with 240 receiving interventions in the one-stop clinic. The average amount of time spent per visit was shortened from four hours to two and a half hours with an average of three interventions on the same day, versus one previously. Of the patients who received interventions, 84.8% were satisfied with the hybrid telemedicine model and 80.8% of them had reported a maintained or improved quality of life after being enrolled in the program. Discussion: Telemedicine has been widely adopted during the pandemic, but older adults with limited digital literacy may find it a challenge. Our hybrid telemedicine model has allowed us to continue to provide cancer care, identify issues brought about by social isolation, and render timely assistance. It has become imperative to adapt, prepare and plan for the challenges we may face amid the ongoing COVID-19 pandemic and similar future outbreaks. Only by doing so can we remain agile and resilient, to continue providing quality care to our older patients with cancer.